2018
DOI: 10.4067/s0718-40262018000200117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de Síndrome de Burnout en un Centro de Cirugía Académico-Asistencial Público en Chile

Abstract: Material and Method: Cross-sectional study. 19 medical interns, 11 surgical residents and 15 surgeons of Hernán Henríquez Aravena Hospital and surgery department of Universidad de La Frontera were included. Applied instrument: MBI questionnaire in its adaptation of the Spanish population. Calculation of measures of central tendency and percentage, as well as comparison of variables through t Student and values of Cronbach's alpha coefficients were performed. Results: Regarding the MBI scale, the overall preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
0
2
0
15
Order By: Relevance
“…According to the subscales, the prevalence of Emotional exhaustion was 76%, low Personal accomplishment at work 55%, and Depersonalization 62%. 15 And based on an integrative review of 106 studies, studies showing medium levels of burnout mostly revealed low to moderate Emotional exhaustion, low Depersonalization and moderate Personal accomplishment. 5 In the research context, the scores for Emotional exhaustion and Depersonalization were significantly high, and low for Personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the subscales, the prevalence of Emotional exhaustion was 76%, low Personal accomplishment at work 55%, and Depersonalization 62%. 15 And based on an integrative review of 106 studies, studies showing medium levels of burnout mostly revealed low to moderate Emotional exhaustion, low Depersonalization and moderate Personal accomplishment. 5 In the research context, the scores for Emotional exhaustion and Depersonalization were significantly high, and low for Personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, se argumentan que a menor edad la falta de experiencia, problemas de identidad, socialización, expectativas irreales del rol profesional y falta de apoyo pueden incidir en el desarrollo del SB. Otros autores (17), consideran que ser hombres, casados, tener hijos, no realizar turnos de urgencia, actúan como factores protectores de Burnout, lo que coincide con otras investigaciones en Latinoamérica.…”
Section: Discussionunclassified
“…ISSN 2616 -6097, Rev Peru Investig Salud, 2022, 6(1), enero -marzo:[17][18][19][20][21][22] Caracterización del burnout en médicos del Hospital Provincial de Portoviejo, Manabí, Ecuador, durante la pandemia…”
unclassified
“…1,[4][5][6][7] Ese fenómeno, además de afectar el bienestar personal del médico, puede impactar indirectamente en la calidad de atención de los pacientes. 1 Pese a eso, se desconoce la presencia de burnout en traumatólogos dentro de Chile y Latinoamérica, 14 por lo que el objetivo principal de este estudio fue evaluar el auto-reporte de dicho fenómeno en traumatólogos que ejercen en Chile.…”
Section: Discussionunclassified